Erectile Dysfunction in Heme-Deficient Nitric Oxide–Unresponsive Soluble Guanylate Cyclase Knock-In Mice. Issue 2 (1st February 2017) - Decaluwé, Kelly; Pauwels, Bart; Boydens, Charlotte; Thoonen, Robrecht; Buys, Emmanuel S.; Brouckaert, Peter; Van de Voorde, Johan
Abstract: Introduction: The nitric oxide (NO), soluble guanylate cyclase (sGC), and cyclic guanosine monophosphate (cGMP) pathway is the leading pathway in penile erection. Aim: To assess erectile function in a mouse model in which sGC is deficient in heme (apo-sGC) and unresponsive to NO. Methods: Mutant mice (sGCβ1 ki/ki ) that express an sGC enzyme that retains basal activity but fails to respond to NO because of heme deficiency (apo-sGC) were used. Isolated corpora cavernosa from sGCβ1 ki/ki and wild-type mice were mounted in vitro for isometric tension recordings in response to sGC-dependent and -independent vasorelaxant agents. In addition, the erectile effects of some of these agents were tested in vivo at intracavernosal injection. Main Outcome Measures: In vitro and in vivo recordings of erectile responses in sGCβ1 ki/ki and wild-type mice after stimulation with sGC-dependent and -independent vasorelaxant agents. Results: NO-induced responses were abolished in sGCβ1 ki/ki mice in vitro and in vivo. The ability of the heme-dependent, NO-independent sGC stimulator BAY 41-2272 to relax the corpora cavernosa was markedly attenuated in sGCβ1 ki/ki mice. In contrast, the relaxation response to the heme- and NO-independent sGC activator BAY 58-2667 was significantly enhanced in sGCβ1 ki/ki mice. The relaxing effect of sGC-independent vasorelaxant agents was similar in wild-type and sGCβ1 ki/ki mice, illustrating that the observed alterations in vasorelaxation are limited to NO-sGC-cGMP–mediated processes. Conclusion: Our results suggest that sGC is the sole target of NO in erectile physiology. Furthermore, this study provides indirect evidence that, in addition to sGCα1 β1, sGCα2 β1 is important for erectile function. In addition, the significant relaxation observed in sGCβ1 ki/ki mice with the cumulative addition of the sGC activator BAY 58-2667 indicates that sGC activators might offer value in treating erectile dysfunction.